Aqidah Akhlak Learning in the Merdeka Curriculum at MTs and MA: An Analysis of Content Breadth and Dept - Abdullah Abdullah; Agus Satria; Rabiatul Ismi; Metha Lanenia; Dahliana Ariz Kartika Sari (The Future of Education Journal, 2026)
This study aims to analyze the breadth and depth of Aqidah Akhlak materials in the Merdeka Curriculum at the MTs/MA level based on the structure of learning outcomes in phases D, E, and F. The study employed a qualitative approach using library research. The primary source of data was the Decree of the Director General of Islamic Education Number 9941 of 2025 concerning Learning Outcomes for Islamic Religious Education and Arabic Language in Madrasahs, supported by scientific journals, books, and other relevant documents. Data analysis was conducted using content analysis through data reduction, categorization, interpretation, and conclusion drawing based on Jean Piaget’s cognitive development theory and the revised Bloom’s Taxonomy. The findings indicate that the learning outcomes of Aqidah Akhlak are systematically, progressively, and sustainably designed in accordance with students’ cognitive, emotional, social, and spiritual development. Phase D focuses on strengthening moral and spiritual foundations, Phase E emphasizes analytical abilities toward Islamic sources, while Phase F develops critical, reflective, and contextual thinking skills in addressing socio-religious issues. Process skills also develop progressively from observing to analyzing, evaluating, and communicating solutions based on Islamic values. This study confirms that the Merdeka Curriculum in Aqidah Akhlak supports character building, religious moderation, and the development of higher order thinking skills (HOTS), although its implementation still faces challenges related to teachers’ pedagogical competence and madrasah readiness.